A virtual culinary medicine intervention for ethnically diverse individuals with type 2 diabetes: development of the Nourishing the Community through Culinary Medicine - Macias-Navarro, Lorena; McWhorter, John Wesley; Guevara, Diana C.; Bentley, Sarah S.; Sharma, Shreela V.; Torres, Jennifer H.; Ai, David; Heredia, Natalia I. (Frontiers in Nutrition, 2024)
Virtual culinary medicine education interventions have the potential to improve dietary be-haviors, nutrition knowledge, cooking skills, and health outcomes for ethnically diverse indi-viduals with type 2 diabetes. The purpose of this study is to describe the adaptation of the Nour-ishing the Community through Culinary Medicine (NCCM) program for virtual delivery, and the protocol for pilot testing this intervention. The intervention included five 90-minute virtual NCCM sessions streamed live from a Teaching Kitchen. Feasibility outcomes were recruitment, retention, acceptability, and satisfaction. Short-term effectiveness outcomes were measured through self-administered questionnaires, including perceived health, average daily servings of fruits and vegetables, frequency of healthy food consumption, shopping, cooking, and eating behaviors, cooking self-efficacy, diabetes self-management, perceived barriers to healthy eating, and nutrition knowledge. Demographics and biometric outcomes were sourced from the patient’s electronic medical records including glycosylated hemoglobin (HbA1c), Body Mass Index, and blood pressure. We will conduct a single-arm pilot study to test the feasibility and short-term effectiveness of NCCM program with individuals with type 2 diabetes.